Perancangan UI/UX Website Perpustakaan Daerah Kota Jayapura sebagai Upaya Digitalisasi Sistem Peminjaman Buku Fisik - Aura Rezlina Zatalini; Betha Almanfaluthfi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
This study aims to design the UI/UX of the Jayapura Regional Library website to improve accessibility and simplify the physical book borrowing service through a digital platform. Low literacy rates in Papua, combined with the limitations of the existing OPAC system that can only be accessed on-site, underscore the need for a more flexible digital solution. The design process applies the Design Thinking method encompassing empathize, define, ideate, prototype, and test stages. Data were collected through in-depth interviews with library users and staff, as well as direct observation of the OPAC system. The interface was designed using Figma in the form of wireframes, mockups, and interactive prototypes. The design incorporates an earth-tone color palette inspired by the visual character of Jayapura, Plus Jakarta Sans typography, and a mobile-first layout approach. Usability testing involving 24 respondents yielded a mean System Usability Scale (SUS) score of 80, categorized as Excellent. All respondents (100%) agreed that the website simplifies book searching, makes borrowing more practical, and improves the overall library service experience compared to the existing conventional system.